2013
DOI: 10.1155/2013/743034
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Flow over Wavy Horizontal Surface

Abstract: In this paper boundary layer analysis is performed over a heated horizontal wavy surface. The governing boundary layer equations are transformed into parabolic partial differential equations with the help of appropriate coordinate transformation. Parabolic partial differential equations are then solved numerically with finite difference scheme, seeking details of the momentum and energy fields.Step by step computations are done for the upstream, downstream, and entire regimes. The numerical results are thoroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Tiny obstacles can be made larger resulting in wavy, undulating surfaces. A numerical boundary layer analysis is performed over a heated horizontal wavy surface, 30 where it was concluded that surface geometry (undulations) plays a vital role in controlling heat transfer rate. Similarly, in Raayai-Ardakani and McKinley, 31 the effects of periodic sinusoidal riblet surfaces aligned in the flow direction (also known as a ''wrinkled'' texture) on the evolution of a laminar boundary layer flow are explored.…”
Section: Passive Flow Controlmentioning
confidence: 99%
“…Tiny obstacles can be made larger resulting in wavy, undulating surfaces. A numerical boundary layer analysis is performed over a heated horizontal wavy surface, 30 where it was concluded that surface geometry (undulations) plays a vital role in controlling heat transfer rate. Similarly, in Raayai-Ardakani and McKinley, 31 the effects of periodic sinusoidal riblet surfaces aligned in the flow direction (also known as a ''wrinkled'' texture) on the evolution of a laminar boundary layer flow are explored.…”
Section: Passive Flow Controlmentioning
confidence: 99%
“…The use of surface waviness to increase the natural convective heat transfer from horizontal surfaces has been quite extensively investigated in the past, e.g., see [1][2][3][4][5][6][7], and the use of waves with a triangular crosssectional shape in this configuration has received quite significant attention. However, the results of the studies of the use of triangular shaped waves indicate that under some conditions such a wave shape does not produce as great an increase in the heat transfer rate as would be anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Siddiqa and Hossain [21] analyzed convective flow. Siddiqa et al [22] illustrated free convective flow past radiative wavy surface.…”
Section: Introductionmentioning
confidence: 99%